Identifying problems with data collection at a local level: survey of NHS maternity units in England. Issue 7210 (4th September 1999) - Kenney, Natalie; Macfarlane, Alison
Abstract: Objectives: To document the extent to which maternity data are collected and how they are recorded, and to identify problems that may affect their availability throughout the NHS. Methods: Postal survey in September 1997 with structured questionnaires. Setting: 207 NHS trusts with maternity units in England. Participants: Heads of midwifery in maternity units. Main outcome measures: Extent to which maternity data were routinely recorded, how they were recorded and evaluated, and to whom they were made available. Results: 167 (81%) of questionnaires were returned, representing 166 trusts. Of these trusts, 165 collected ≥17 of the 19 data items in HES maternity tail, and 158 collected ≥40 of the 45 items selected from Körner dataset. Only 18 collected all five items selected from the "indicators of success, " and 17 did not collect any. In 58 of trusts data were primarily recorded on paper. A computerised maternity information system was used by 106 (63%) of trusts, but many recorded data on paper first. Thirty four did not audit data for accuracy. Most trusts analysed data not routinely collected at national level, but 18 did not analyse HES maternity tail and 17 did not analyse Körner data. Conclusions: Improvement is needed in quality, completeness, and availability of maternity data at a national level, particularly if the NHS information strategy is to be successfully implemented. Although most of the data items in national datasets are recorded locally, variations in the way data are defined, recorded, and analysed and lack of linkage between computer systems restrict their access, availability, and use at local, district, and national levels.